Comparison of short‐term outcomes following minimally invasive versus open Sweet esophagectomy for Siewert type II adenocarcinoma of the esophagogastric junction. Issue 6 (1st April 2020) - Sun, Xiaohui; Wang, Gaoxiang; Liu, Changqing; Xiong, Ran; Wu, Hanran; Xie, Mingran; Xu, Shibin
Abstract : Background: Surgical resection is still the main treatment option for patients with resectable Siewert type II adenocarcinoma of the esophagogastric junction (AEG). This retrospective study evaluated the significance of minimally invasive Sweet esophagectomy (MISE) for the treatment of Siewert type II AEG. Methods: We retrospectively evaluated 174 patients with Siewert type II AEG who received a Sweet esophagectomy in our center between October 2013 and September 2017. Of these patients, 73 underwent MISE and 101 underwent open Sweet esophagectomy (OSE). The clinicopathologic factors, operational factors and postoperative complications were compared. Results: The two groups were similar in terms of age, sex, American Society of Anesthesiologists grade, preoperative staging and incidence of comorbidities ( P  > 0.05). Relative to the OSE approach, the MISE approach was associated with a significant decrease in surgical blood loss ( P  < 0.001), chest tube duration ( P = 0.003) and postoperative admission duration ( P = 0.002). The minimally invasive approach was associated with significantly less total morbidity and fewer respiratory complications than the open approach ( P = 0.015 and P = 0.016, respectively). Relative to the open approach, the MISE approach was associated with a significant increase in the number of total lymph nodes removed and the locations of the total lymph nodes removed ( P  < 0.001 and P  < 0.001, respectively). Conclusions: Our MISE technique can be safely and effectively performed for intrathoracic anastomosis with favorable early outcomes.